VD_FINDINFO Décision / 2015 / 267 vom 2. März 2015 - VD Tribunal cantonal (2015)
OPPOSITIONPROCÉDURE, JUGEMENT PAR DÉFAUT, MOTIVATION DE LA DEMANDE | 356 al. 4 CPP (CH), 385 CPP (CH), 393 al. 1 let. b CPP (CH)